Connected consciousness after tracheal intubation in young adults: an international multicentre cohort study. (February 2023) - Lennertz, Richard; Pryor, Kane O.; Raz, Aeyal; Parker, Maggie; Bonhomme, Vincent; Schuller, Peter; Schneider, Gerhard; Moore, Matt; Coburn, Mark; Root, James C.; Emerson, Jacqueline M.; Hohmann, Alexandra L.; et al.
Abstract: Background: Connected consciousness, assessed by response to command, occurs in at least 5% of general anaesthetic procedures and perhaps more often in young people. Our primary objective was to establish the incidence of connected consciousness after tracheal intubation in young people aged 18–40 yr. The secondary objectives were to assess the nature of these responses, identify relevant risk factors, and determine their relationship to postoperative outcomes. Methods: This was an international, multicentre prospective cohort study using the isolated forearm technique to assess connected consciousness shortly after tracheal intubation. Results: Of 344 enrolled subjects, 338 completed the study (mean age, 30 [standard deviation, 6.3] yr; 232 [69%] female). Responses after intubation occurred in 37/338 subjects (11%). Females (13%, 31/232) responded more often than males (6%, 6/106). In logistic regression, the risk of responsiveness was increased with female sex (odds ratio [ORadjusted ]=2.7; 95% confidence interval [CI], 1.1–7.6; P =0.022) and was decreased with continuous anaesthesia before laryngoscopy (ORadjusted =0.43; 95% CI, 0.20–0.96; P =0.041). Responses were more likely to occur after a command to respond (and not to nonsense, 13 subjects) than after a nonsense statement (and not to command, four subjects, P =0.049). Conclusions: Connected consciousness occured after intubation in 11% of young adults, with females at increased risk. Continuous exposure to anaesthesia between induction of anaesthesia and tracheal intubation should be considered to reduce the incidence of connected consciousness. Further research is required to understand sex-related differences in the risk of connected consciousness.